Body Composition and Bone Health During Hypoenergetic Diet- and Exercise-induced Weight Loss Are Enhanced by Diets Higher in Dairy Foods and Dietary Protein - Josse, Andrea R. (My University, 2011)
Obesity is a major health concern. Strategies to reduce obesity including weight loss by energy restriction have disease risk reduction benefits, however, energy restriction alone often leads to the loss of muscle mass. Muscle is a very important tissues in the body particularly from a metabolic standpoint, thus, efforts to maintain it by promoting weight loss with the greatest ratio of fat:lean mass loss should be implemented. Also, bone health may be negatively affected by weight loss if hypoenergetic diets are suboptimal in calcium. Hence, the objective of this thesis was to determine how hypoenergetic diets varying in protein (amount and type) with exercise impacted the composition of weight lost and bone health in premenopausal, overweight and obese women. Ninety women were randomized to three groups (n=30/group): HiDairyPro, DairyPro and Control, differing in the quantity of total protein consumed (30%, 15% or 15% of energy, respectively) and the amount from dairy foods (high, moderate or low, respectively). Body composition was measured by DXA and fourier-transform near infrared spectroscopy (FT-NIR) at 0, 8 and 16 weeks, and visceral adipose tissue by MRI (n=39) at 0 and 16 weeks. Blood and urine samples were taken at 0 and 16 weeks. All groups lost similar body weight, but HiDairyPro lost significantly more total and visceral fat, and gained significantly more lean mass than Control (Chapter 2). HiDairyPro significantly improved bone health and vitamin D status compared to Control (Chapter 3). DXA and FT-NIR measured fat mass correlated and agreed well with each other (Chapter 4). Therefore, diet- and exercise-induced weight loss with higher protein and dairy promoted more favourable body composition changes and improved bone health versus diets with lower protein and no dairy. These data have strong implications for the design of weight loss programs to combat obesity.
Keywords: Body Composition; Bone Health; Dairy; Higher Protein; Exercise; Weight Loss; Exercise Science; Human and Clinical Nutrition; Exercise Science